Analysis of Manning's and Drag Coefficients for Flexible Submerged Vegetation - Wan Yusof, K. (Institute of Physics Publishing, 2017)
Accurate determination of flow resistance is of great significance in modelling of open channels that will convey water efficiently. Although, resistance or drag induced by vegetation have been systematically studied for several decades, estimating of the resistance remain as a challenge. This is because most of previous studies use artificial vegetation to investigate flow - vegetation interactions. To overcome this, the present study evaluates the vegetation resistance in terms of Manning's roughness coefficient and drag coefficient using a natural flexible vegetation (cow grass) under submerged condition. From the experimental result obtained, it was observed that the Manning's and drag coefficients decreased with the increasing in average velocity. Also, graphical relationship between Manning's coefficient, n and drag coefficient, CD has been developed with R2 = 0.9465, which indicate that there exist a strong correlation between n and CD, and one can use the proposed graphical model to predict the n - values corresponding to the CD - values. © Published under licence by IOP Publishing Ltd.